The Journalist'sToolbox : A Guide to Digital Rep.orting and Al - Reilley Mike (new york : Routledge Taylor and Francis Group., 2024)
Focusing on the "how" and "why" of digital rep.orting, this interactive textbook equip.s readers with all the skills they need to succeed in today$1 (Bs multimedia rep.orting landscap.e. The Journalist$1 (Bs Toolbox is an extension of the JournalistsToolbox.ai website, which p.rovides links to tools, organized by beats and top.ics, as well as social channels, a newsletter, and more than 95 training videos relevant to journalists. This handbook offers a deep. dive into these digital resources, exp.laining how they can be manip.ulated to build multimedia stories online and in broadcast. It covers all the basics of data journalism, fact-checking, using social media, editing and ethics, as well as video, p.hoto, and audio p.roduction and storytelling. The book considers digital journalism from a global p.ersp.ective, including examp.les and interviews with journalists from around the world. p.acked full of hands-on exercises and insider tip.s, The Journalist$1 (Bs Toolbox is an essential comp.anion for students of online/digital journalism, multimedia storytelling and advanced rep.orting. This book will also make an ideal reference for p.racticing journalists looking to hone their craft. This book is sup.p.orted by training videos, interactive charts and a p.op.-up. glossary of key terms which are available as p.art of an interactive e-book+ or online for those using the p.rint book.s
Keywords: The Journaliste